THE TRIBAL PROBLEM BETWEEN IRAQ AND IRAN (1925–1960): A DOCUMENTARY STUDY –JAF TRIBE AS A SAMPLE** - Yousif, Fakhir (Humanities Journal of University of Zakho, 2025)
The Jaf tribe is considered one of the most influential and historically significant Kurdish tribes. Branches of this tribe live across both Iraqi and Iranian territories. This study, titled "The Tribal Problem between Iraq and Iran (1925–1960): A Documentary Study – Jaf Tribe as a Sample", focuses specifically on the Iraqi Kurdish branches of the Jaf tribe residing within the borders of Kurdistan, Iraq. Since many members of the Iraqi Jaf tribe worked as pastoralists and livestock herders, they frequently crossed into Iranian Kurdistan in search of pastures and grazing lands for their animals. This recurrent movement often led to disputes and tensions with Iranian authorities and local Kurdish leaders in Iranian Kurdistan. During the Pahlavi era, the Iranian government responded to these incursions by either attempting to expel them or imposing grazing and pasture taxes on them when they entered Iranian territory. The issue is well-documented in Persian archival records from both the First and Second Pahlavi periods. This study examines the Iranian government’s response to the cross-border movement of the Iraqi Jaf tribe, particularly in Kurdish regions of Iran, using and analyzing unpublished Persian archival documents. The research adopts a descriptive-analytical method and relies on both library-based sources and documentary evidence.